Penerapan Community-Based Tourism di Desa Budo, Kabupaten Minahasa Utara - Amelya Navratilova; Geraldine C. D Podung; Jasho E. A Kalampung (Warta Pariwisata, 2023)
Budo Tourism Village is located in North Minahasa Regency, North Sulawesi. This tourist village which is included in the top 50 at the 2022 Indonesian Tourism Village Award (ADWI) has tourism potential in the form of natural and cultural attractions. The Budo Tourism Village was initiated by the village community by working with the government and academics to develop their tourism potential into tourist attractions and encourage the formation of tourist destinations which then gave birth to tourism activities whose management is carried out by the community (community-based tourism). The research was conducted to determine how far the implementation of Community-Based Tourism was carried out in the Budo Tourism Village based on the 10 stages of Community-Based Tourism Development.